Information flows and aggregate persistence - Oleksiy Kryvtsov (Bank of Canada, 2009)
Models with imperfect information that generate persistent monetary nonneutrality predominantly rely on assumptions leading to substantial heterogeneity of information across price-setters. This paper develops a quantitative general equilibrium model in which the degree of heterogeneity of information is determined endogenously. In the model, firms use two technologies to acquire information: costly updating to full information and costless learning from publicly observed market signals. Price changes of firms that update information infrequently are synchronized with market signals. This leads to an externality whereby less frequent updating increases the information conveyed by prices and quantities. When the model is calibrated to moments from a panel of BLS commodity sectors, it is found that the private value of costly updating to full information is close to zero, market signals are informative, and the real effects of monetary shocks are small.
Keywords: D83; E31; E32; 330; Business fluctuations and cycles; Inflation and prices; ransmission of monetary policy; Betriebliche Preispolitik; Unvollkommene Information; Geldpolitik; Schock; Transmissionsmechanismus; Theorie